MARKETING STRATEGY SUCCESS: A CASE STUDY OF PT AVIA AVIAN TBK. - Sukoco, Regina Yolanda; Waluyowati, Nur Prima; Handrito, Radityo Putro (Erudio Journal of Educational Innovation, 2026)
According to the Indonesian Central Bureau of Statistics (BPS) 2025 report, Indonesia’s economy exhibited sustained growth throughout the 2022–2024 period. This macroeconomic stability has served as a primary catalyst for the expansion of various industrial sectors. This phenomenon positively correlates with the expansion of diverse industrial sectors, notably within the construction industry. Concurrently, strategic opportunities within the building materials market have experienced significant growth, with the decorative coatings (paint) segment emerging as a particularly high-potential vertical. This potential is evidenced by the persistent market share competition between prominent domestic and multinational brands. Notably, the strategic marketing initiatives executed by PT Avia Avian Tbk. have yielded superior outcomes relative to competitors employing analogous frameworks. Despite intensive market saturation, PT Avia Avian Tbk. has maintained its position as a dominant domestic entity within the Indonesian retail paint segment. The primary objective of this research is to evaluate and delineate the underlying drivers of PT Avia Avian Tbk.'s market leadership. Adopting a qualitative case study methodology—specifically an explanatory single-case embedded design, the study utilizes primary data gathered through semi-structured interviews with ten key persons both internal and external stakeholders. The findings indicate that PT Avia Avian Tbk.’s competitive dominance is predicated upon a robust, integrated distribution infrastructure, complemented by iterative product innovation and asymmetric marketing strategies. These three pillars collectively facilitate a sustainable competitive advantage within the retail landscape.